2011
DOI: 10.1080/14675986.2011.567072
|View full text |Cite
|
Sign up to set email alerts
|

School‐based human rights education: case studies in Hong Kong secondary schools

Abstract: In an era of rapid globalization, space and time are seriously compressed. People from different nations, cultures, religions and other backgrounds have become much more interconnected and interdependent. Since people are rapidly intermingling, what values should be considered as standards and norms in regulating this situation, so that people of different backgrounds can relate peacefully to each other with mutual respect? United Nations (UN) human rights standards could be considered as sets of shared global… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
1
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 8 publications
1
22
1
4
Order By: Relevance
“…Such beliefs may have led to a fear that HRE could pose a threat to school discipline (item 46). This echoes the findings of Leung, Yuen, and Chong (2011), Reilly and Niens (2005), and Ruane et al (2010). The generally positive attitudes, together with the misconceptions, seem to suggest that although LS teachers had a certain understanding of the importance and meaning of human rights and value human rights in principle, they had reservations in upholding human rights in real life situations, especially when they perceived human rights as threatening to their interests.…”
Section: Intercultural Education 349supporting
confidence: 92%
See 1 more Smart Citation
“…Such beliefs may have led to a fear that HRE could pose a threat to school discipline (item 46). This echoes the findings of Leung, Yuen, and Chong (2011), Reilly and Niens (2005), and Ruane et al (2010). The generally positive attitudes, together with the misconceptions, seem to suggest that although LS teachers had a certain understanding of the importance and meaning of human rights and value human rights in principle, they had reservations in upholding human rights in real life situations, especially when they perceived human rights as threatening to their interests.…”
Section: Intercultural Education 349supporting
confidence: 92%
“…A project on Education for Human Rights and the Rule of Law Teachers, who teach LS, in particular human rights, face many challenges, including insufficient knowledge, difficulties in maintaining student interest, tailor-making of school-based curriculum, adopting issue-based approaches, assessment, and the concern about the misuse of human rights concepts (Leung, Yuen, and Chong 2011;Lo 2010). In view of these difficulties, a two-year (June 2009-July 2011) 'Basic Law Education Project' was launched by the HKIEd to support teachers.…”
Section: A Brief Portrait Of Human Rights and Hre In Hong Kongmentioning
confidence: 99%
“…Most of these studies reveal the positive impact of both the incorporation of HRE into the curriculum and its successful implementation, as evidenced by student competencies (Bajaj 2012;Covell 2010;Hayashi 2011;Leung et al 2011;Magbitang-Chauhan et al 2000;Nordin et al 2011). However, some findings have revealed that students, despite having experienced HRE courses, feel powerless in facilitating their own or other people's human rights (Çayır, Bağlı 2011).…”
Section: The Understanding Of Hre By Students In Schools In Terms Of mentioning
confidence: 99%
“…For example, Howe and Covell (2005) have argued that teachers' often adopt a negative approach to CRE and Figue (2013) and Leung et al (2011) report that many teachers see children's rights as a threat to adult authority (thus failing to understand the appropriate role of adult duty bearers). Thus teacher training becomes a key recommendation in many reports on HRE and CRE (Burridge et al, 2013;DIHR, 2013;HRC, 2014;Morgan and Kitching 2006;UNHCHR, 2010).…”
Section: Teachers As Implementersmentioning
confidence: 99%